Trading Volume and Cross‐Autocorrelations in Stock Returns - Chordia, Tarun; Swaminathan, Bhaskaran (Journal of Finance, 2000)
This paper finds that trading volume is a significant determinant of the lead‐lag patterns observed in stock returns. Daily and weekly returns on high volume portfolios lead returns on low volume portfolios, controlling for firm size. Nonsynchronous trading or low volume portfolio autocorrelations cannot explain these findings. These patterns arise because returns on low volume portfolios respond more slowly to information in market returns. The speed of adjustment of individual stocks confirms these findings. Overall, the results indicate that differential speed of adjustment to information is a significant source of the cross‐autocorrelation patterns in short‐horizon stock returns.